ANALYSIS OF USAGE OF 4C LEARNING SKILLS IN PHYSICS STUDENT WORKSHEETS CLASS XI SEMESTER 2 IN SOLOK DISTRICT AND CITY - Aspo Ramadhan; Nanang Winarno; Yenny Darvina (Universitas Negeri Padang, 2022)
One of the implementations of the 2013 curriculum is to apply 4C skills in classroom learning using LKS. Applying 4Cs to Student Worksheets can help students practice 4C skills. Observation results show that the worksheets used in high schools in Solok Regency and City vary, and the use of 4C skills is not yet known. The objective is to analyze 4C skills on Student Worksheet Class XI Physics Semester 2 in the District and Solok. This type of research is descriptive research with a qualitative approach. The population of this research is all physics worksheets for students of class XI State Senior High School Semester 2 used in Solok Regency and City. The sample of this study was the Physics LKS of SMA Class XI Semester 2, which was designed and used by physics teachers at State Senior High Schools in Solok Regency and City. The research data were taken through documentation studies and interviews. The data processing technique in this study was Content Analysis. Based on the results of the study, it was concluded that the use of 4C skills on the Physics Student Worksheets for Class XI Semester 2 in Solok Regency and City was still low, with the category of less facilitating. The average percentage obtained from the use of 4C learning skills in each component is as follows. Critical thinking 31.9%, creativethinking 19.47%, communication 21.68%, and collaboration 14.84%